Designing a toolkit for assessing the financial and investment potential of enterprises for the implementation of energy saving measures - Prokhorova, Viktoriia; Yemelyanov, Olexandr; Koleshchuk, Orest; Shepelenko, Svitlana; Slastianykova, Krystyna; Havras, Dmytro (Eastern-European Journal of Enterprise Technologies, 2026)
This work assesses the financial and investment potential of enterprises for implementing energy-saving measures. The task addressed is to design an effective toolset for such an assessment. This study has made it possible to contribute to solving this task. Specifically, components in the financial and investment potential of enterprises in implementing energy-saving measures have been identified. Indicators for assessing the specified potential and its components were constructed. It was proposed to carry out such an assessment in several stages using an optimization approach. The designed toolset was tested on a sample of 105 enterprises belonging to three energy-intensive industries. The financial and investment potential of the studied enterprises in implementing energy-saving measures was assessed. It was established that the main limiting factor of the magnitude of this potential is its financial component. The level of use of this potential by the studied companies was calculated. It was found that this level for enterprises with high energy intensity of production varies by industry from 37.19% to 44.29%. It was found that with increasing energy efficiency, the size of the financial and investment potential of the studied enterprises for their implementation of energy-saving measures decreases but the level of realization of this potential increases. The proposed toolkit is suitable for use both at the level of individual companies and at the industry level. Its application could allow company managers to more reasonably approach the development of financial and investment strategies for implementing energy-saving measures